Plantar Pressure Changes and Correlating Risk Factors in Chinese Patients with Type 2 Diabetes: Preliminary 2-year Results of a Prospective Study - Xuan Qiu; De-Hu Tian; Chang-Ling Han; Wei Chen; Zhan-Jian Wang; Zhen-Yun Mu; Kuan-Zhi Liu (Chinese Medical Journal, 2015)
Background: Plantar pressure serves as a key factor for predicting ulceration in the feet of diabetes patients. We designed this study to analyze plantar pressure changes and correlating risk factors in Chinese patients with type 2 diabetes. Methods: We recruited 65 patients with type 2 diabetes. They were invited to participate in the second wave 2 years later. The patients completed identical examinations at the baseline point and 2 years later. We obtained maximum force, maximum pressure, impulse, pressure-time integral, and loading rate values from 10 foot regions. We collected data on six history-based variables, six anthropometric variables, and four metabolic variables of the patients. Results: Over the course of the study, significant plantar pressure increases in some forefoot portions were identified (P < 0.05), especially in the second to forth metatarsal heads. Decreases in heel impulse and pressure-time integral levels were also found (P < 0.05). Plantar pressure parameters increased with body mass index (BMI) levels. Hemoglobin A1c (HbA1c) changes were positively correlated with maximum force (β = 0.364, P = 0.001) and maximum pressure (β = 0.366, P = 0.002) changes in the first metatarsal head. Cholesterol changes were positively correlated with impulse changes in the lateral portion of the heel (β = 0.179, P = 0.072) and pressure-time integral changes in the second metatarsal head (β = 0.236, P = 0.020). Ankle-brachial index (ABI) changes were positively correlated with maximum force changes in the first metatarsal head (β = 0.137, P = 0.048). Neuropathy symptom score (NSS) and common peroneal nerve sensory nerve conduction velocity (SCV) changes were positively correlated with some plantar pressure changes. In addition, plantar pressure changes had a correlation with the appearance of infections, blisters (β = 0.244, P = 0.014), and calluses over the course of the study. Conclusions: We should pay attention to the BMI, HbA1c, cholesterol, ABI, SCV, and NSS changes in the process of preventing high plantar pressure and ulceration. Some associated precautions may be taken with the appearance of infections, blisters, and calluses.